2003
DOI: 10.1093/brain/awg147
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling identifies responder and non‐responder phenotypes to interferon‐β in multiple sclerosis

Abstract: Autoimmune diseases such as multiple sclerosis are characterized by complex genetic traits and pathomechanisms that translate into clinical heterogeneity. This wide heterogeneity of multiple sclerosis as well as different biological responses to immunomodulatory drugs can be expected to contribute to differential treatment responses. Strategies that dissect the relationship between the treatment response and the biological characteristics in individual patients are valuable not only as a clinical tool, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 32 publications
7
93
0
Order By: Relevance
“…An interesting conclusion held by the author is the exclusion of the hypothesis that interferon β treatment in MS actually shifts immunity from a Th1 to Th2 shift. This is in concordance with the work of Wandinger (Wandinger et al, 2001 andSturzebecher et al, 2003). Sturzebecher investigated the gene expression profile of PBMCs ex vivo and in vitro from 10 RRMS patients with interferon therapy.…”
Section: Major Peripheral Blood Mononuclear Cell Gene Expression Micrsupporting
confidence: 83%
“…An interesting conclusion held by the author is the exclusion of the hypothesis that interferon β treatment in MS actually shifts immunity from a Th1 to Th2 shift. This is in concordance with the work of Wandinger (Wandinger et al, 2001 andSturzebecher et al, 2003). Sturzebecher investigated the gene expression profile of PBMCs ex vivo and in vitro from 10 RRMS patients with interferon therapy.…”
Section: Major Peripheral Blood Mononuclear Cell Gene Expression Micrsupporting
confidence: 83%
“…Our study has detected a significant inhibition of IL-17C expression, which was recently reported to induce STAT3 expression, and in cooperation with RORgt and RORa induces Th17 cell differentiation and enhances EAE disease activity (37). Multiple studies have reported on the IFN-b treatment-induced gene expression changes in RRMS patients (38)(39)(40), however our study reports on the Th17 gene expression changes in CIS patients following IFN-b-1a therapy. The findings are consistent with the results of Durelli et al (11), who reported that Th17 cells have a higher IFNAR1 expression than Th1 cells and are selectively susceptible to inhibition by IFN-b-1a.…”
Section: Ifn-b-1a Treatment Of Rrms Patients Induced Ifnar1 Signalingmentioning
confidence: 50%
“…40,41 As anticipated, the one patient receiving IFN-b therapy clustered together with the RRMS high patients and showed an upregulation of IFN-induced genes. Although transcription-based prediction of IFN-b therapy has been studied, 42,43 future research in a large cohort of patients is needed to sort out whether the absence or presence of a type-I IFN response in the PB of patients with RRMS is a prognostic factor for successful treatment with IFN-b.…”
Section: Discussionmentioning
confidence: 99%